2011
DOI: 10.1021/jp207487z
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of α-Sexithiophene on Friction-Transferred Polythiophene Film

Abstract: Controlling the molecular orientation of the conjugated oligomer, α-sexithiophene (6T), is crucial to improve organic optoelectronic device performance. Most 6T molecules evaporated onto quartz and SiO(2)/Si substrates orient nearly perpendicular to the substrate. Here, we report the formation of oriented thin films of 6T on in-plane-oriented polythiophene (PT) films formed by the friction-transfer method. 6T was evaporated onto oriented PT films under vacuum. The films were investigated by polarized optical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…This molecular anisotropy and consequently anisotropic electron mobility can be used advantageously in circuit design, for example, to isolate neighboring components without requiring a large spatial separation or the patterning of the semiconductor layer [34]. In addition, in organic photovoltaic devices, where bias voltage is applied between top and bottom electrodes, it is expected that the increase in mobility due to crystal alignment in the direction perpendicular to the substrate will lead to improved power conversion efficiencies [35]. An example of this effect has been demonstrated in the use of a porous alumina template to prepare vertically aligned core-shell nanorods of P3HT and PCBM from the melt [22].…”
Section: Tmentioning
confidence: 99%
See 1 more Smart Citation
“…This molecular anisotropy and consequently anisotropic electron mobility can be used advantageously in circuit design, for example, to isolate neighboring components without requiring a large spatial separation or the patterning of the semiconductor layer [34]. In addition, in organic photovoltaic devices, where bias voltage is applied between top and bottom electrodes, it is expected that the increase in mobility due to crystal alignment in the direction perpendicular to the substrate will lead to improved power conversion efficiencies [35]. An example of this effect has been demonstrated in the use of a porous alumina template to prepare vertically aligned core-shell nanorods of P3HT and PCBM from the melt [22].…”
Section: Tmentioning
confidence: 99%
“…Mizokuru et al [35] reported the formation of oriented thin films of the oligothiophene ␣-sexithiophene (6T) deposited on to in-plane-oriented polythiophene (PT) films formed by friction-transfer. Thin films of 6T were evaporated onto an oriented 5 nm thick PT film, itself friction transferred at 250 • C, under vacuum.…”
Section: Friction Transfermentioning
confidence: 99%
“…We have already reported usages of friction-transferred PT films as orienting substrates for other semiconducting molecules [ 35 , 36 , 37 , 38 ]…”
Section: Introductionmentioning
confidence: 99%
“…31 Anisotropic substrates such as TiO 2 (11 0) 32,33 and Cu(11 0), 34,35 friction transferred poly-(tetrafluoroethylene) a) Author to whom correspondence should be addressed. Electronic mail: fbalzer@mci.sdu.dk (PTFE) and polythiophene, 36,37 and nanoporous substrates [38][39][40] have been used in the past as templates to form uniaxially aligned entities from organic molecules. Here, muscovite mica is used as a model substrate.…”
Section: Introductionmentioning
confidence: 99%